Pengembangan Teknologi Mikroenkapsulasi Bakteri Probiotik dan Manfaatnya untuk Kesehatan (TECHNOLOGY DEVELOPMENT OF PROBIOTIC BACTERIA MICROENCAPSULATION AND IT BENEFIT FOR HEALTHY) - Setiarto, Raden Haryo Bimo; Kusumaningrum, Harsi Dewantari; Jenie, Betty Sri Laksmi; Khusniati, Tatik (Jurnal Veteriner; Vol 19 No 4 (2018), 2019)
Probiotic based products are associated with many health benefits. However, the main problem is the low survival of these probiotic in food products as well as in gastrointestinal tract. Providing probiotics with a physical barrier is an efficient approach to maintain microorganisms and to deliver them into the gut. Microencapsulation is one of the most efficient methods, and it has been under consideration and investigation by some researcher. Generally, the success of this technology is depend on the quality of the wall material, probiotic strain, the core release form and the encapsulation method. Therefore, in this review, some relevant microencapsulation aspects, such as the capsule, wall material, core release forms, encapsulation methods will be briefly discussed. In this sense, microencapsulation has gained an increasing interest, since it has been demonstrated that it could protect the destruction of bacteria not only during its production process but also during its delivery into gastrointestinal tract, as well as it function as a protective effects during storage.